Village Economic Potential Mapping as a Basis for Determining Regional Investment Priorities in Tolitoli Regency: Pemetaan Potensi Ekonomi Desa sebagai Dasar Penentuan Prioritas Investasi Daerah di Kabupaten Tolitoli - Andhy Saputra; Alfansyah Fathur; Julistyono Widodo; Mardiana Rahim (STIE MUJAHIDIN TOLITOLI, 2026)
This study aims to map the economic potential of villages as a basis for determining regional investment priorities in Tolitoli Regency, Central Sulawesi, Indonesia. The study addresses the need for a more systematic identification of local economic resources to support effective investment planning and regional economic development. A descriptive quantitative approach was employed using secondary data obtained from official publications of the Statistics Indonesia Office of Tolitoli Regency, including Village Potential Statistics, Gross Regional Domestic Product by Industry, and other regional statistical reports. Data were analyzed through descriptive analysis, economic sector identification, and village potential mapping to determine sectors with the greatest investment prospects. The findings reveal that agriculture remains the dominant economic activity in most villages and urban villages of Tolitoli Regency, indicating a strong dependence on primary-sector activities. The study also finds that the availability of business financing facilities, telecommunications infrastructure, and village economic institutions provides supportive conditions for investment development. Based on the mapping results, agriculture and its related subsectors, particularly plantations, livestock, and fisheries, emerge as the most strategic sectors for regional investment prioritization. The study concludes that village economic potential mapping can provide an important foundation for formulating investment policies that are more aligned with local economic characteristics and regional development objectives.